Global research status and intelligent technology development trend of open-pit mining blasting: visualization analysis based on CiteSpace and VOSviewer - Jie Tan; Weiming Guan; Anye Cao; Changxin Wang; ZiZhao Zhang; Yun Duan; Hui Chen (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract Blasting is an important process in open-pit mining, and blasting technology directly affects the efficiency, cost and ecology of mine production. Research on blasting in open-pit mining has been progressing, but there is a lack of systematic discussion of the current status of its research and future directions. Therefore, in this study, CiteSpace and VOSviewer were used to visualize and analyze 446 documents in the field of open-pit mining blasting technology in the Web of Science database from January 1999 to July 2024 and to summarise the current history of the field's development, journals, research collaborations, and research hotspots and trends. The research results indicate that the current research hotspots are "blast vibration," "prediction," "model," and others. Numerical simulation and machine learning are key research directions driving continuous innovation and intelligent development in open-pit mining blasting technology. On this basis, the applications of numerical simulation and machine learning in this field are systematically reviewed. New research methods for open-pit mining blasting technology are proposed by integrating the advantages of both numerical simulation and machine learning techniques.